ANALISIS PEMBERDAYAAN MASYARAKAT KECAMATAN ILIR TIMUR I KOTA PALEMBANG DALAM RANGKA MENDUKUNG VISI PALEMBANG EMAS - Devri Rumambi Awuy; Devi Apriyanti; Ferdiansyah Ferdiansyah; Freydy Dwija Atmaja; Heri Surapati (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
Community Empowerment is an effort to develop the independence and welfare of the community by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing resources through the establishment of policies, programs, activities and assistance in accordance with the essence of the problem and priority needs of the community. This study aims to analyze the Community Empowerment of Ilir Timur I Subdistrict, Palembang City in Supporting the Vision of Golden Palembang. Data collection techniques used are observation, interviews and documentation. While the analysis technique used in this study is a qualitative data analysis technique. From the results of the study, it can be seen that the Lurah Success Assessment Program has not yet been realized, which is due to the unprepared instrument for disclosing data and the value of village development. The Village Assessment Program has not yet been realized, which is due to the unprepared instrument for disclosing data and the value of village development. The Village Community Empowerment Program has not yet been realized because the Kelurahan competition was only attended by 3 Kelurahan, and the number of participants who attended was 197 people. To improve these weaknesses, it is expected to prepare implementing elements, both from related parties and from the community who can help prepare instruments for disclosing data and values of kelurahan development. Prepare implementing elements, both from related parties and from the community who can help prepare instruments for disclosing data and values of kelurahan development. Increase socialization regarding activities that will be carried out in Village Community Empowerment. So that the community can find out about Village Community Empowerment activities that will be carried out at the sub-district and village levels.